The sentimental and financial journey of women navigating e-commerce - Mayur Vyas; Piyush Mehta (The Scientific Temper, 2025)
Electronic commerce is the full form of e-commerce. This is the interface that provides services and products, either free or paid. This is a virtual online mode that provides an environment including business platforms, transactions, and digitalization. When we talk about the sentimental and financial situation of women who are the users of e-commerce, it is significant to look outside the transactional nature of e-commerce to study how it impacts the experience of women both psychologically and commercially. This paper explores the sentimental and financial journey of women engaged in e-commerce, focusing on the ways that online platforms are switching their roles in business, society, and personal life. During the past ten years, e-commerce has become a convincing method for women to succeed in financial freedom, create entrepreneurial attempts, and defeat traditional barriers to appear present in the corporate world. However, the economic impact is not the individual benefit. This paper also investigates the emotional revolution experienced by women, such as enhanced self-confidence, inspiration, and a sense of execution that comes with running and topping online businesses and how they manage time management. This paper uses information from case studies, interviews, and surveys to explore how women manage their e-commerce businesses while balancing financial goals and personal happiness. It looks at the difficulties women face in the mostly male-led online business world, such as gender bias, lack of digital skills, and the challenge of managing both work and family life. At the same time, the paper shows the emotional benefits women gain—like feeling more independent, being able to express themselves, and building connections with others. By looking at both the money women earn and the emotional satisfaction they feel, this study gives a full picture of how e-commerce can change women’s lives. It shows that online businesses can help women become financially independent and grow stronger emotionally. The paper also suggests ways to better support women in the online business world, such as offering special training, mentoring, and policy changes to reduce gender gaps in e-commerce. This research adds to the bigger discussion about women’s rights and how digital business can help bring more fairness between men and women in the global economy.